Simultaneous Regulation on Solvation Shell and Electrode Interface for Dendrite‐Free Zn Ion Batteries Achieved by a Low‐Cost Glucose Additive - Sun, Peng; Ma, Liang; Zhou, Wanhai; Qiu, Meijia; Wang, Zilong; Chao, Dongliang; Mai, Wenjie (Angewandte Chemie International Edition, 2021)
Dendrite growth and by‐products in Zn metal aqueous batteries have impeded their development as promising energy storage devices. We utilize a low‐cost additive, glucose, to modulate the typical ZnSO4 electrolyte system for improving reversible plating/stripping on Zn anode for high‐performance Zn ion batteries (ZIBs). Combing experimental characterizations and theoretical calculations, we show that the glucose in ZnSO4 aqueous environment can simultaneously modulate solvation structure of Zn2+ and Zn anode‐electrolyte interface. The electrolyte engineering can alternate one H2O molecule from the primary Zn2+‐6H2O solvation shell and restraining side reactions due to the decomposition of active water. Concomitantly, glucose molecules are inclined to absorb on the surface of Zn anode, suppressing the random growth of Zn dendrite. As a proof of concept, a symmetric cell and Zn‐MnO2 full cell with glucose electrolyte achieve boosted stability than that with pure ZnSO4 electrolyte. A low‐cost glucose additive into traditional ZnSO4 electrolyte can greatly inhibit the dendrite growth on Zn anodes in Zn ion batteries by simultaneously modulating the solvation shell in the electrolyte and electrode interface.